Mycovirome of Diaporthe helianthi and D. gulyae, causal agents of Phomopsis stem canker of sunflower (Helianthus annuus L.) - Chien-Fu Wu; Elizabeth Regedanz; Febina Mathew; Ruchika Kashyap; Karthika Mohan; Shin-Yi Lee Marzano (Virus Research)
Diaporthe gulyae and D. helianthi cause Phomopsis stem canker, which is a yield-limiting fungal disease of sunflower (Helianthus annuus L.) in the United States. In this study, the mycovirus population was characterized in D. gulyae and D. helianthi using 52 and 42 isolates, respectively, that were recovered from diseased sunflower plants randomly sampled from commercial sunflower fields in the U.S. states of Minnesota, Nebraska, North Dakota, and South Dakota. Total RNA extracts depleted of rRNA from each fungus were pooled to construct one library for sequencing to obtain 20 GB per library of raw reads using a metatranscriptomics approach. Only the family Mitoviridae was present in both Diaporthe species. Twelve and nine novel viral contigs were discovered infecting D. gulyae and D. helianthi, respectively. Additionally, we detected two of the same viruses infecting D. helianthi, Helianthus annuus leaf-associated partitivirus 3 and 5, that were detected in a direct sunflower metatranscriptome reported before. Interestingly, Qinvirus, which is mostly known as a group of insect viruses, was found in a contig. An ambivirus that is rarely reported in the phylum Ascomycota was also discovered in this study. Besides an understanding of virome diversity, the mycovirome survey provides the first clue of biological molecules that can be further developed for antifungal purposes.